ANALISIS FLYPAPER EFFECT PADA BELANJA DAERAH KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH - Subadriyah subadriyah; Solikhul Hidayat (Universitas Ahmad Dahlan, 2018)
This study aims to determine the effect of PAD and DAU on Regional Expenditure as well as to determine whether there a flypaper effect on the Districts / Cities in Central Java Province. This research is a quantitative research with population of 35 districts / cities located in Central Java province. The sampling technique is by census method. The method of analysis used is multiple regression analysis. Secondary data is taken from the Realization Report of Regional Income and Expenditure Budget in 2015. The result shows that PAD and DAU partially have significant effect to local expenditure and flypaper effect has occurred in Districts/City in Central Java Province. This means that the district / cities governments in Central Java are still dependent on the central government in terms of financing local spending.Keywords: PAD, DAU, Flypaper Effect